Answer:
g(x) = x^2/16
Step-by-step explanation:
To stretch a function horizontally by a factor of k, replace x with x/k.
You want a stretch factor of 4, so your function is ...
g(x) = f(x/4) = (x/4)^2
g(x) = x^2/16
__
The attached graph shows the horizontal stretch.
Remember
(x^m)(x^n)=x^(m+n)
and difference of 2 perfect squres
(a²-b²)=(a-b)(a+b)
and sum or difference of 2 perfect cubes
so
(x^3)(x^3)(x^3)=x^(3+3+3)=x^9
so
x^9=3*3*x^3
x^9=9x^3
minus 9x^3 both sides
0=x^9-9x^3
factor
0=(x^3)(x^6-9)
factor difference of 2 perfect squraes
0=(x^3)(x^3-3)(x^3+3)
factor differnce or sum of 2 perfect cubes (force 3 into (∛3)³)
0=(x³)(x-∛3)(x²+x∛3+∛9)(x+∛3)(x²-x∛3+∛9)
set each to zero
x³=0
x=0
x-∛3=0
x=∛3
x²+x∛3+∛9=0 has no solution
x+∛3=0
x=-∛3
x²-x∛3+∛9=0 has no solution
so the solutions are
x=-∛3, 0, ∛3
AnswerD
Step-by-step explanation:
Answer: x² + y² - 2x - 8y + 13 = 0
Step-by-step explanation:
the equation of the circle is in the form (x - a)² + (y - b)² = r²
where (a,b) is the center of the circle and r is the radius
hence the equation is
(x - 1)² + (y - 4)² = 2²
x²-2x+1+y²-8y+16= 4
x²+ y² -2x- 8y + 17 =4
x² + y² - 2x - 8y = -13
x² + y² - 2x - 8y + 13 = 0
Answer:
57.8
Step-by-step explanation: